Experiência de estágio supervisionado na educação infantil: interações, brincadeiras e organização do trabalho pedagógico - LINHARES, Ana Paula Santos (2023)
This research presented here in the Course Completion Work is the result of the experience on the supervised internship in early childhood education, at the Nursery and Pre-School Professora Ana Sousa de Oliveira, of the Pedagogy course at the Faculty of Education, Campos Universitário de Bragança, Federal University from Pará. The central objectives characterize the educational context of the institution, located in the municipality of Bragança-PA; describe the school routine in a preschool I class; present the didactic-pedagogical intervention carried out during the internship; and reflect on the contribution of this curricular activity to teacher training as an intern. This experience took me as a researcher outside the university, and mademe observe the environment that has the role of socializing knowledge and the duty of acting in the moral formation of students, it is this sum of effort that promotes the full development of the individual as a citizen. And it was from the projects used in the school that led me to know the true reality of the day care center, and how I could learn and contribute to the school community, during my internship. As it is the only institution in the municipality and offers Daycare and Pre-Schools, priority has been given to children from needy families, with the aim of caring for and educating the child as a whole. Over the years, the demand for a place at the school grew, the enrollment criteria underwent adjustments, the subjects of the school were redesigned, now serving children from various neighborhoods of the city, different financial conditions and also children with disabilities. The methodology of technological resources was worked on, which the students were already adapted to, at the request of the teacher, as all the planning of the classes had already been done. Fairy tales and numerals were being worked on. Considering that the teacher used videos to reinforce what she had already taught. In this experience I had a lot to learn. However, I was able to observe that for a day care center and preschool, literacy was worked a lot, little use of assisted games was observed, with the aim of teaching, and we know that in the early years, games have a lot of meaning in relation to learning. . However, the practice of the internship brought significant contributions to our knowledge, it was a possibility of maturing both personally and professionally, because when relating to previously unknown people, it was necessary to put into practice ethics, respect and interaction with other professionals for the good development in the work environment. The experience lived in the internship made us reflect on our training and our performance as future education professionals. How can we improve our work together with children, especially with regard to the learning process and child development? These questions were only possible to be thought from the rich experience coming from the supervised internship in early childhood education.